2005
DOI: 10.1016/j.socscimed.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Spousal influence on smoking behaviors in a US community sample of newly married couples

Abstract: Among married couples, partners often have similar characteristics and behaviors. Among individuals who smoke cigarettes, it is not uncommon for them to have a partner who also smokes. In fact, having a partner who smokes can influence the spouse's initiation of smoking, or return to smoking after a previous quit attempt. Additionally, it is possible that a nonsmoking partner can influence his/her spouse to stop smoking. Participants for this research are from a community sample of couples in the United States… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
131
1
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 67 publications
13
131
1
14
Order By: Relevance
“…As hypothesized, we found evidence that on days with higher emotional and instrumental support receipt and provision, women and men cut down on their own daily number of cigarettes smoked (actor effects for women and men). Because smokers with a partner who also smokes have lower quit success 6 , it is remarkable that this study replicates from a prior study of smoker-nonsmoker couples showing the central role of social support after a quit attempt. Results of this study confirmed that it is equally beneficial for female and male smokers to receive emotional and instrumental support from their partners.…”
Section: Accepted Manuscriptsupporting
confidence: 70%
See 3 more Smart Citations
“…As hypothesized, we found evidence that on days with higher emotional and instrumental support receipt and provision, women and men cut down on their own daily number of cigarettes smoked (actor effects for women and men). Because smokers with a partner who also smokes have lower quit success 6 , it is remarkable that this study replicates from a prior study of smoker-nonsmoker couples showing the central role of social support after a quit attempt. Results of this study confirmed that it is equally beneficial for female and male smokers to receive emotional and instrumental support from their partners.…”
Section: Accepted Manuscriptsupporting
confidence: 70%
“…4,5 Among individuals who smoke, it is not uncommon for them to have a partner who also smokes. 4,6 Individuals tend to exhibit health behaviors similar to their spouses. 4,7 Furthermore, spouses or romantic partners have considerable influence on health behavior change 8 , including smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In the US, Homish et al found the prevalence of smoking to be 32% in males and 28% in females. 12 In our study, probably, first research done in female and male marriage applicants in Turkey.…”
Section: Resultsmentioning
confidence: 83%